Characterization of a vacuolar sucrose transporter, HbSUT5, from Hevea brasiliensis: involvement in latex production through regulation of intracellular sucrose transport in the bark and laticifers - Xiangyu Long; Heping Li; Jianghua Yang; Lusheng Xin; Yongjun Fang; Bin He; Debao Huang; Chaorong Tang (BMC Plant Biology, 2019)
Abstract Background Sucrose (Suc), as the precursor molecule for rubber biosynthesis in Hevea brasiliensis, is transported via phloem-mediated long-distance transport from leaves to laticifers in trunk bark, where latex (cytoplasm of laticifers) is tapped for rubber. In our previous report, six Suc transporter (SUT) genes have been cloned in Hevea tree, among which HbSUT3 is verified to play an active role in Suc loading to the laticifers. In this study, another latex-abundant SUT isoform, HbSUT5, with expressions only inferior to HbSUT3 was characterized especially for its roles in latex production. Results Both phylogenetic analysis and subcellular localization identify HbSUT5 as a tonoplast-localized SUT protein under the SUT4-clade (=type III). Suc uptake assay in baker’s yeast reveals HbSUT5 to be a typical Suc-H+ symporter, but its high affinity for Suc (Km = 2.03 mM at pH 5.5) and the similar efficiency in transporting both Suc and maltose making it a peculiar SUT under the SUT4-clade. At the transcript level, HbSUT5 is abundantly and preferentially expressed in Hevea barks. The transcripts of HbSUT5 are conspicuously decreased both in Hevea latex and bark by two yield-stimulating treatments of tapping and ethephon, the patterns of which are contrary to HbSUT3. Under the ethephon treatment, the Suc level in latex cytosol decreases significantly, but that in latex lutoids (polydispersed vacuoles) changes little, suggesting a role of the decreased HbSUT5 expression in Suc compartmentalization in the lutoids and thus enhancing the Suc sink strength in laticifers. Conclusions Our findings provide insights into the roles of a vacuolar sucrose transporter, HbSUT5, in Suc exchange between lutoids and cytosol in rubber-producing laticifers.